The Effect of Hemodialysis Implementation on Blood Pressure of Patients Undergoing Hemodialysis at Bhayangkara Hospital Class I PUSDOKKES Polri - Dewi , Nurma; Hombing, Veronika Boru; Manikam, Ratna Mutu (LPPM Universitas Mohammad Husni Thamrin, 2025)
Background: Hemodialysis is currently experiencing quite rapid development, but many patients still experience medical problems while undergoing HD. Complications that also often occur in patients undergoing HD are hemodynamic disorders. Hemodynamics is the flow of blood in our body's circulatory system, either through magna circulation (large circulation) or parva circulation (circulation in the lungs). Hemodynamics is the state of work functions such as heart and lung function. The purpose of this study was to determine the effect of hemodialysis implementation on blood pressure of patients undergoing hemodialysis at Bhayangkara Hospital TK. I Pusdokkes Polri Method: the research design was one group pretest-posttest conducted from May 2024 to August 2024. The sample in this study amounted to 136 respondents with a sampling technique using purposive sampling. Results: the average systolic blood pressure of patients before undergoing HD was 134.04 mmHg and the average diastolic blood pressure of patients before undergoing HD was 88.40 mmHg. The average systolic blood pressure of patients after undergoing HD was 129.66 mmHg and the average diastolic blood pressure of patients after undergoing HD was 86.41 mmHg. There is an effect of hemodialysis implementation on the systolic blood pressure of patients (p = 0.000). There is an effect of hemodialysis implementation on the diastolic blood pressure of patients (p = 0.010). Conclusion: GGK patients undergoing hemodialysis can affect the hemodynamic status of HD patients. The results of this study can describe the occurrence of blood pressure changes that occur in patients undergoing hemodialysis, so that patient monitoring can be further improved